The effectiveness of a functional movement screen as a tool to predict cervical and trunk injuries in male university American football players: A prospective study - Takito, M.; Nagai-Tanima, M.; Aoyama, T. (Sports Orthopaedics and Traumatology, 2025)
Summary Objective To examine the effectiveness of a Functional Movement Screen for predicting cervical and trunk injuries in male university American football players. Material and methods The study targeted 66 male players of the Kyoto University American Football Club. The Functional Movement Screen was administered in preseason July 2021 and scored using a 4-point scale. The occurrences of injuries during practice and games were recorded over a one-year period from pre-season to post-season. The participants were divided into injury and non-injury groups. Results The study included 66 participants, of whom 61 experienced injuries. A total of 22 and 44 players were classified into the injury and non-injury groups, respectively. Among them, 22 players defined as cervical and trunk injuries, including non-contact and contact indirect injuries. There was not a significant difference in total score of Functional Movement Screen, but the sub-score of Functional Movement Screen "Deep Squat" was significantly lower in cervical and trunk injury group (p<0.05). There was no significant difference in other sub-score. Conclusions Among the seven movements of Functional Movement Screen, only the Deep Squat showed the potential for predicting cervical and trunk injuries. Limitations in ankle dorsiflexion and trunk mobility may result in dangerous tackling postures, increasing the risk of injury due to repeated contact. Zusammenfassung Zielsetzung Untersuchung der Effektivität eines Functional Movement Screens für die Bezifferung der Erwartbarkeit von Hals- und Rumpfverletzungen bei männlichen Spielern einer American-Football-Universitätsmannschaft. Material und Methoden Die Studie schloss 66 männliche Spieler des Kyoto University American Football Clubs ein. Der auf einer 4-Punkte-Skala basierende Functional Movement Screen wurde in der Vorsaison im Juli 2021 angewendet. Das Auftreten von Verletzungen während des Trainings und bei Spielen wurde über eine Zeit von einem Jahr zwischen Vorsaison und Nachsaison aufgezeichnet. Die Studienteilnehmer wurden in Gruppen mit Verletzungen und ohne Verletzungen eingeteilt. Ergebnisse Die Studie schloss 66 Teilnehmer ein, von denen 61 Verletzungen aufwiesen. Insgesamt 22 bzw. 44 Spieler wurden jeweils in die Gruppen mit und ohne Verletzungen eingeteilt. Darunter befanden sich 22 Spieler mit Hals- und Rumpfverletzungen, kontaktlose und indirekte Kontaktverletzungen eingeschlossen. Es wurde keine signifikante Differenz im jeweiligen Gesamtscore des Functional Movement Screens gemessen, allerdings lag das Teilergebnis "tiefe Kniebeuge" des Functional Movement Screens in der Gruppe Hals- und Rumpfverletzungen signifikant niedriger (p < 0.05). In keinem der anderen Teilergebnisse konnte eine signifikante Differenz gemessen werden. Fazit Von den sieben Bewegungsmustern des Functional Movement Screens konnte lediglich für das Teilergebnis "tiefe Kniebeuge" ein Potential zur Bezifferung der Erwartbarkeit von Hals- und Rumpfverletzungen gezeigt werden. Einschränkungen in der Dorsalflexion des Fußgelenks und in der Rumpfmobilität können zu gefährlichen Tacklingbewegungen führen und so das Verletzungsrisiko aufgrund von wiederholtem Kontakt erhöhen. Autorreferat